VERIFICATION OF SURFACE RUN-OFF VOLUME PREDICTION WITH STATISTICAL DOWNSCALING METHOD BY USING CLIMATE FORECAST SYSTEM VERSION 2 OUTPUT (Case Study: PT. Adaro) - APRILIA ERNITA (NIM : 12813014), CHARLA
Surface runoff is one of the factors causing flood. PT. Adaro discharges waste to Tabalong and Balangan Sub-basin outlets. Kementrian Lingkungan Hidup dan Kehutanan (KLHK) reports that there was a waste flood in Balangan River causing environmental damage in 2009. Based on this, the prediction of surface runoff volume needs to be conducted as waste disposal management to the river. CFSv2 is one of the seasonal predictions that can predict surface runoff volume. In this study there are two schemes to predict surface runoff volume The results showed slightly different values of Brier Score (BS) between corrected CFSv2 and raw CFSv2 in both schemes. Scheme prediction 1 using water suface run-off variable has a BS values ranging from 0,5 to 0,7 and positive BSS values, although in some decades it has negative Brier Skill Score (BSS) values which indicate a low prediction accuracy in predicting high surface runoff volumes at both Sub-basins. While the prediction of scheme 2 using variable prate (rainfall), corrected CFSv2 has a fairly good accuracy based on BS values with ranging from 0,32 Ã‚Â– 0,46 and all decades have positive BSS values. Thus, scheme 2 can be considered to predict the volume of surface runoff as a waste disposal management of PT. Adaro.